Extra-Articular Endoscopy. Issue 1 (March 2016) - Doral, Mahmut N.; Huri, Gazi; Bohacek, Ivan; Turhan, Egemen; Bojanic, Ivan
Abstract : With the advent of endoscopy in the last 2 decades, a number of procedures, and modifications to them, have been developed and have advanced exponentially. The list of indications was extended over time because of several reasons: better understanding of the pathophysiology, better diagnostics, and advances in endoscopic technology. In this review article, we summarize the most frequently performed extra-articular endoscopic procedures on the extremities. As there are several methods, some have been described briefly, whereas others have been described in greater detail, such as suprascapular nerve entrapment syndrome and Achilles tendon disorders, as they present our area of interest and subspecialty domain. Recent advances in the treatment of versatile pathologic entities have been described, together with new methods, which currently lack sufficient clinical data but still represent promising techniques for the future.